Diagnostic Value of Lactate Dehydrogenase and Uric Acid as Screening Tools for Malignancies in Children - Oriaifo, Irene A; Gerard, James M; Thomas, Scott M (Pediatric emergency care, 2022)
The aim of this study was to determine the diagnostic value of lactate dehydrogenase (LDH) and uric acid (UA) in children undergoing evaluation for possible malignancies. This was a retrospective chart review of patients aged 0 to 18 years presenting to an urban, tertiary care, pediatric hospital between July 1, 2011, and July 1, 2016. Patients were included if they had an LDH and/or UA level drawn, and they were excluded if they had a known cancer diagnosis. Sensitivity, specificity, and receiver operating characteristic curves were calculated for each biomarker. Six hundred five subjects were included in this study; 579 and 384 subjects had LDH and UA levels drawn, respectively; 15.7% had a final diagnosis of malignancy (49 leukemia, 46 nonleukemia). The specificities of both biomarkers for all types of malignancies were lower than their respective sensitivities. Comparing leukemic versus nonleukemic malignancies, the areas under the curve were 0.848 and 0.719, respectively, for LDH and 0.681 and 0.555, respectively, for UA.